If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 7 = 2x + 3 Reorder the terms: 7 + 1x = 2x + 3 Reorder the terms: 7 + 1x = 3 + 2x Solving 7 + 1x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + 1x + -2x = 3 + 2x + -2x Combine like terms: 1x + -2x = -1x 7 + -1x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -1x = 3 + 0 7 + -1x = 3 Add '-7' to each side of the equation. 7 + -7 + -1x = 3 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 3 + -7 -1x = 3 + -7 Combine like terms: 3 + -7 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 6+(5+8)*4= | | 3x-4-x=6x-12 | | 6x-29=5x-7 | | 15x-8x=40+9 | | 5p^2-6=7p | | -10-3c=10+9c | | 6x+4=8x-7(-x+3)-4x | | -11x+43=-34 | | 2x^67=9r | | 12-x=-32 | | 22-5r=2r | | x^2+x=4.27 | | 6p+5=17 | | 2(x^2-7x+21)=0 | | 502.4=3.14(4)h | | Y-x=-9 | | 30+x=167 | | .5(2n-3)-.1=.4(6+2n) | | 5*8+6y=94 | | 15-8x=49 | | 8q-q=14 | | 1.7+7n=9.5-4n | | 3(5x-9)=-2(6-2x)+2 | | 5b-27-23b=7 | | -5x-15=(-30) | | 25x+5*5=125 | | 2p^2-2p-40=0 | | -(4+a)=3a | | 4(3-5x)=-5(3x+3) | | 9t-3=15 | | -11=9-5 | | 180=9x+1+8x+9 |